Horseman in Senegal, photo postcard by Joannès Barbier - Joannès Barbier (Wikimedia Commons, 1890)
Carte postale ancienne issue de Wikimedia Commons. Titre: Horseman in Senegal, photo postcard by Joannès Barbier. Horseman in Senegal, photo postcard by Joannès Barbier. The horseman is Madior Tioro Fall, son of Damel Madiodio Déguen Coddou. [1] Summary of the history before this photo: History given with the photo breaks down into the following: Diambor revolt (Dec 1856-Dec 1859), a rivalry between "the Fall Tié Ndela and the Fall Madior Tioro." [1] Who they were Fall Tié Ndela was also Damel Tié Ndela. He was the son of Macodou. [1] Fall Madior Tioro was the son of Damel Madiodio Déguen Coddou. He was the great grandson of Amari Ngoné Ndela Coumba. [1] How it started The Mboul diaourigne, Amadi Ngaye, who was in favour of Fall Madior, stirred up the Diambours against Damel Tié Ndela. [1] He proclaimed Fall Madior's father, Madiodo, to be Damel (now Damel Madiodo). He allied with Tié Yacine, the Tègne of Baol, he sought to overthrow Biraïma in 1856. [1] He "stirred the Diambors" to be an army, but they were defeated in Mboul. Amadi was killed. [1] What they did After Amadi's death, Damel's brother (Samba Maram Khay) also sought to overthrow Biraïma and become "Diaoudine Mboul". He fled to Saint-Louis, Senegal and incited "all the discontented people of Cayor" against the Damel (Damel Tié Ndela). He raised people from Ndiambour province to rise up--mainly Muslims hostile to Damel Tié Ndela and the Tiédos people. His army entered Guet in Dec. 1859. It burned and pillaged. It caused the Guet leader Silmakha Diop to flee. [1] Damel Tié Ndela was young, and dying when Damel's brother attacked. The young Damel's father (Macodou) counterattacked using an army of Tiédos. He defeated the army of the Diambours and burned their main village, Louga. This ended the Diambour revolt. [1]
Droits : Licence Public domain via Wikimedia Commons
Keywords: carte postale; image; patrimoine; histoire locale; wikimedia commons; Carte postale